Gourd, Okeechobee—Cucurbita okeechobeensis Bailey - James M. Stephens (EDIS)
This document describes the Okeechobee gourd (Cucurbita okeechobeensis), a rare native plant found primarily along the southeastern shore of Lake Okeechobee in Florida. It details the plant’s climbing growth habit, distinctive grape-like foliage, and hard-shelled, nearly globular fruits. The article highlights the gourd’s threatened status due to habitat disturbance and cold weather, and notes its limited distribution and lack of known edibility. Original publication date May 1994.